Clinical evaluation of education relating to nutrition and skeletal loading in competitive male road cyclists at risk of relative energy deficiency in sports (RED-S): 6-month randomised controlled trial. Issue 1 (29th March 2019) - Keay, Nicola; Francis, Gavin; Entwistle, Ian; Hind, Karen
Abstract : Objective: To clinically evaluate education to improve eating behaviour and skeletal loading exercise in male cyclists at risk of poor bone health and impaired performance due to relative energy deficiency in sports. Methods: Early race season, 50 competitive male road cyclists were matched, in pairs, based on Z-scores for lumbar spine bone mineral density (BMD). One member of each pair was randomly allocated to receive educational interventions. After the season, 45 cyclists returned for dual-energy X-ray absorptiometry scans and blood tests. Least significant change was applied to identify clinically meaningful BMD changes. Cyclists completed a follow-up sport-specific questionnaire and clinical interview to ascertain adherence to the interventions. Results: The questionnaire and clinical interview categorised behaviour changes as positive, negative or unchanged. Positive changes in nutrition and skeletal loading were associated with a statistically significant increase of 2.0% in lumbar spine BMD; 7 of 11 cyclists' increases were clinically meaningful. Negative changes in both behaviours were associated with a significant decrease of 2.7% in lumbar BMD; all nine cyclists' BMD decreases were clinically meaningful. Regarding performance, taking account of functional threshold power, changes in nutritional behaviour accounted for gains or losses of 95 British Cycling racing points. Cyclists reported psychological barriers to change in behaviours, specifically fear of negatively impacting performance. Conclusions: Educational nutritional and skeletal loading interventions can improve bone health, well-being and race performance in male cyclists over a 6-month race season. Psychological support may be required to help some athletes change behaviour.